ROLE OF MEDIA IN DISASTER MANAGEMENT - Kapoor, Neelam (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2015)
The media forges a direct link between the public and emergency organizations and plays a very important role in disseminating vital information to the public before, during and after disasters. The media assists in the management of disasters by educating the public about disasters; warningm of hazards; gathering and transmitting information about affected areas; alerting government officials, relief organizations and the public to specific needs; and facilitating discussions about disaster preparedness and response for continuous improvement. To help the media fulfill these roles, direct working relationships between the media and disaster management organizations should be established and maintained. Experience shows that regular interactions with the mediabefore a disaster strikes, aids the effective flow of information and lays the groundwork for effective working relationships in the aftermath of a disaster. 1 The Press Day on November 16, 2000 was observed with the theme of “Role of Media in Disaster Management – Preparing People to Cope with Disasters.” A National Seminar was organised at Vigyan Bhawan, New Delhi, which was inaugurated by the President of India. In his inaugural address, the Hon’ble President emphasized the need for disseminating preparedness aspects of disaster management among all sections of society and making special provisions for the more vulnerable sections of the community viz. women and children.